Pengaruh Model Pembelajaran Make A Match Terhadap Hasil Belajar Bahasa Indonesia Pada Siswa Kelas II MIN 2 Kota Tangerang - Meyliana Putri; Hindun Hindun (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of using the make a match learning model on the learning outcomes of Indonesian language for second-grade students at MIN 2 Kota Tangerang. The research method employed is a Quasi-Experiment with a Nonequivalent Control Group design. The study involves two classes, namely the experimental class and the control class. The sample consists of all students in class II A (experimental class) and students in class II B (control class). In the experimental class, students are treated with the make a match learning model, while in the control class, students are treated with the lecture learning model. Data collection is conducted through pre-tests and post-tests, as well as observations of learning activities. The results of this research indicate a positive and significant influence on the application of the make a match learning model on the learning outcomes of second-grade students at MIN 2 Kota Tangerang in the subject of Indonesian language. The influence can be seen from the difference in learning outcomes between the experimental class and the control class.